Genomic organization of TEL: the human ETS-variant gene 6. - Baens, M; Peeters, P; Guo, C; Aerssens, J; Marynen, P

(untitled) (Genome Research, 1996)
We have constructed a detailed map of the genomic region containing the ETS-variant gene 6 (ETV6), involved in translocations and deletions associated with hematologic malignancies. Thirty-eight cosmids were characterized belonging to two contigs spanning 340 kb, and an EcoRl restriction map was developed. The gap between the two contigs, 2 kb in size, was closed by PCR. The contigs contain the complete coding sequence and the 5' and 3' UTRs of ETV6. Eight exons accounting for the ETV6 cDNA sequence were identified. The helix-loop-helix (HLH) motif is coded by exons 3 and 4, whereas exons 6-8 code for the ETS DNA-binding domain. All introns show consensus 5' donor and 3' acceptor splice sites. Introns 1 and 2 span 100 and 82 kb, respectively, and introns 3-7 range from 15 to 1.3 kb. An alternative exon 1 (exon 1B) is localized in intron 2. The 5' end of the ETV6 gene is associated with a CpG island characterized by the presence of four Notl, four Sacll, and three BssHll recognition sites and several SP1- and AP2-binding motifs. Alternative polyadenylation at the 3' end of the ETV6 gene generates the three transcripts of 6200, 4300, and 2400 nucleotides, respectively. The ETV6 gene spans 240 kb and is flanked at its 5' and 3' end by D12S1697 and D12S98, respectively. The markers D12S1095 and D12S89 are located in the first intron. Two new DNA polymorphisms were identified in the ETV6 gene, which will be useful for the analysis of loss of heterozygosity reported for the ETV6 gene in leukemia.